The Psychological Impact of Bullying on Children’s Personalities and Cognitive Development: A Case Study of Saudi Children - Alassaf, Uhuud Fahad (Journal of Educational and Psychological Sciences, 2024)
This research aims to identify the psychological impact of bullying on children’s personalities and cognitive development, a case study of Saudi children. The researcher chose a set of variables (two dependent variables and one independent variable). The dependent variables are Child’s personal development and Child’s cognitive development. And to know its effect on the independent variable (bullying). The sample consisted of (110) individuals from the Kingdom of Saudi Arabia. The model used by the study was interviews as a tool for collecting data related to the study. The Google Docs tool was used to create the questionnaire. The questionnaire is distributed to a large number of people via emails on social media, WhatsApp, Twitter, and Facebook in both Arabic and English. The study discovered a link between bullying children’s personalities and cognitive development the study found a statistically significant relationship between bullying of children’s personalities and cognitive development. This study can help Psychologists, academics, and school principals by taking into account the independent variables in this study.